Genetic divergence between half-sib families of Albizia lebbeck Benth - Wani, Afaq Majid (Indian Journal of Agroforestry, 2020)
The performance of twenty phenotypically superior trees in the natural distribution zones of Uttar Pradesh were studied for genetic divergence. Based on the relative magnitude of D2 values, twenty superior trees progenies were grouped into six clusters on the basis of morphological and biomass traits. Cluster II exhibited the highest number of six superior tree progenies. Cluster II exhibited maximum intra cluster distance (6.60) indicating that progenies in this cluster were more diverse than the other clusters. The maximum inter cluster D2 value was obtained between cluster II and V (61.35). The clustering pattern in this study revealed that superior tree progenies from different geographic region were grouped together in a cluster and vice-versa suggesting that geographical diversity did not necessarily represent the genetic diversity. The contribution of different traits towards diversity revealed that seedling height contributed the maximum towards divergence. Phenotypic coefficient of variation (PCV) was higher than the corresponding genotypic coefficient of variation (GCV) for all the morphological and biomass traits which revealed that the traits were sensitive to environmental fluctuations. The traits with low genetic gain and high heritability indicate that the expression is possibly controlled by intra and inter allelic interactions. The hybridization between the more diverse genotypes of Albizzia lebbeck can produce genotypes with high heterotic vigor.